CD36‐Binding Amphiphilic Nanoparticles for Attenuation of α‐Synuclein‐Induced Microglial Activation. Issue 6 (22nd March 2022) - Zhao, Nanxia; Francis, Nicola L.; Song, Shuang; Kholodovych, Vladyslav; Calvelli, Hannah R.; Hoop, Cody L.; Pang, Zhiping P.; Baum, Jean; Uhrich, Kathryn E.; Moghe, Prabhas V.
Abstract : Neuroinflammation is one of the hallmarks contributing to Parkinson's disease (PD) pathology, where microglial activation occurs as one of the earliest events, triggered by extracellular α‐synuclein (aSYN) binding to the cluster of differentation 36 (CD36) receptor. Herein, CD36‐binding nanoparticles (NPs) containing tartaric acid–based amphiphilic macromolecules (AMs) are rationally designed to inhibit this aSYN–CD36 binding. In silico docking reveals that four AMs with varying alkyl side chain lengths present differential levels of CD36 binding affinity and that an optimal alkyl chain length promotes the strongest inhibitory activity toward aSYN–CD36 interactions. In vitro competitive binding assays indicate that the inhibitory activity of AM‐based NPs plateaus at intermediate side chain lengths of 12 and 18 carbons, supporting the in silico docking predictions. These intermediate‐length AM NPs also has significantly stronger effects on reducing aSYN internalization and inhibiting proinflammatory molecules tumor necrosis factor α (TNF‐α) and nitric oxide from aSYN‐challenged microglia. All four NPs modulate the gene expression of aSYN‐challenged microglia, downregulating proinflammatory genes TNF, interleukin 6 (IL‐6), and IL‐1β, and upregulating anti‐inflammatory genes transforming growth factor β (TGF‐β) and Arg1 expression. Herein, overall, a novel polymeric nanotechnology platform is represented that can be used to modulate aSYN‐induced microglial activation. Abstract : Neuroinflammation is a major contributor to the progression of Parkinson's disease, where binding of the protein alpha synuclein (aSYN) to the cluster of differentiation 36 (CD36) receptor on microglial cells leads to the release of neurotoxic factors that contribute to neuronal death. The authors rationally design tartaric acid‐based amphiphilic nanoparticles to block microglial aSYN–CD36 interactions and attenuate pro‐inflammatory molecules generation.